1986
DOI: 10.1099/00222615-22-4-303
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of toxin production to species in the genus Aeromonas

Abstract: Summary. Ninety-five strains of Aeromonas were divided into three species-A. sobria, A . hydrophila and A . caviae-on the basis of results in 13 biochemical tests. The minimum number of tests necessary to distinguish these species was determined. Culture filtrates of the strains were tested for cytotoxin and cytotonin, haemolysin and protease. One filtrate with high-titre cytotoxin, haemolysin and protease activities was subjected to gel filtration on Sephadex G75 and isoelectric focussing. Of the five cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…However, Charkraborty and colleagues [14] reported that the elongation effect observed in CHO cells was due to a cytotonic enterotoxin and not a cytotoxin. Further, as had been previously shown [34,35], the production of these toxins was significantly related to species, with A. hydrophila and A. sobria being more likely to produce them than A. caviae.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, Charkraborty and colleagues [14] reported that the elongation effect observed in CHO cells was due to a cytotonic enterotoxin and not a cytotoxin. Further, as had been previously shown [34,35], the production of these toxins was significantly related to species, with A. hydrophila and A. sobria being more likely to produce them than A. caviae.…”
Section: Discussionsupporting
confidence: 76%
“…Only 18-9 % of strains gave a positive response at pH 6-0 in the suckling mouse test, compared with 100 % positive at pH 7 4 and 76-9% positive at pH 10 0. Other workers [30,34] have regarded the cytotonic-like effects observed in various cell lines to be due to protease(s). It has been demonstrated that although protease production by A. hydrophila was accompanied by a fall in pH values [46], protease activity was greater at neutral to alkaline than at very acid pH's [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Barer et al [3] considered growth at 42°C a useful characteristic for distinguishing A. sobria from A. hydrophila and A. caviae, but tested growth on horse blood agar, and "the test was considered to be positive only if there was no reduction in size of single colonies by visual comparison with those grown at 37°C. '' This is a very subjective test, and not accurate if indeed colonies, albeit smaller ones, did grow at 42°C.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Growth at 5°C was also strongly correlated with enterotoxigenicity, as 89% of strains which produced enterotoxin also grew at 5°C. Aeromonas species have been found in chlorinated water supplies [3], which may therefore be a source of psychotrophic food spoilage organisms, which are potential human pathogens. Auto-agglutination of strains requires further study to determine whether this is due to the production of surface structures such as pili.…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Aeromonas caviae is associated with gastrointestinal disease in adults and acute, severe gastroenteritis in children [124]. A number of putative virulence factors have been identified for A. caviae , including polar flagella, pili and cytotoxin.…”
Section: Structure Of Carbohydrate Antigens Of Gammaproteobacteriamentioning
confidence: 99%